Filter Series Model for Processing Well Water into Drinking Water in the Milala Residential Area, Central House of Pancurbatu District - Haesti Sembiring; Susanti Perangin-angin; Haryono Haryono; Ibnu Rois (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Many methods of processing well water have been previously studied, but there has been no research aimed at reducing the physical, chemical, and microbiological parameters so that the treated water can be directly consumed. This research aims to determine the appropriate thickness of the series filter media and its ability to process well water into drinking water. This type of research is quasi-experimental with a pre-test post-test design. In the initial stage before the intervention, an examination of the physical parameters (turbidity, color, Total Dissolved Solids/TDS), chemical parameters (iron, manganese, hardness), and microbiological parameters (E. coli bacteria) in well water samples was conducted. In the second stage, changes in water parameters were assessed after treatment using the Parallel Filter Model. The research results show a percentage reduction in turbidity of well water in the Milala Housing Complex in the Pancurbatu Subdistrict, reaching 90.9% - 100%. The percentage reduction in iron (Fe) content of well water in the Milala Housing Complex is 81.9% - 96.2%. The percentage reduction in manganese (Mn) content of well water is 76.9% - 100%. The percentage reduction in water hardness in the Milala Housing Complex is 58.3% - 97.6%, and the reduction in the presence of E. coli in well water occurred in three out of five locations that initially tested positive for E. coli. The series filter is capable of reducing turbidity, iron (Fe), manganese (Mn), the presence of E. coli, and water hardness in well water. Keywords : Drinking water, filter seri, well water treatment